Towards improving the seismic hazard map and the response spectrum for the state of RN/Brazil - Nóbrega,Petrus Gorgônio Bulhões da (2021)
Abstract Although Brazilian seismic activity is defined as low to moderate, it is known that intraplate earthquakes can also be associated to high intensities. In Brazil, the state of Rio Grande do Norte (RN) is one of the most seismically active areas, but there is no specific study to evaluate the seismic hazard in this region. This paper presents analyses towards improving the seismic hazard map, the peak ground acceleration value and the response spectrum of RN. The methodology is based on Probabilistic Seismic Hazard Analysis, comparing the results to the design criteria defined in the Brazilian code NBR 15421:2006 (Design of seismic resistant structures – Procedure). The analyses show that, in general, the code sets conservative values for the peak ground acceleration and for the design response spectrum; however, related to this last one, the shape is quite different.